Kualitas Produk, Harga, Promosi, Dan Penempatan Lokasi Terhadap Minat Konsumen Kafe S-Mart Di Kecamatan Batang Kapas Pesisir Selatan - M Syahfik Willfahni; Maria Magdalena (Universitas Kristen Indonesia Toraja, 2024)
This study aims to determine the influence of product quality, price, location, promotion, and service quality significantly on purchasing decisions at coffee shops in the city of Gresik. The grand theory in this study uses the theory of planned behavior (TPB) and theory of reasoned action (TRA). Researchers use quantitative methods. This method can be used to determine the effect of product quality, price, place, promotion, service quality on purchasing decisions. Product quality, price, place, promotion, service quality are used as independent variables and purchasing decision as dependent variables. In this study, the population used were men and women who lived in Gresik and had visited coffee shops in the city of Gresik with an infinite number. Purposive sampling method with criteria is men or women who live in the city of Gresik and have come to coffee shops in the city of Gresik who consume coffee with the age of 18-34 years. The determination of sample age criteria and sampling locations was based on the target consumers at the Kene Coffee coffee shop and the Honest Docs Team specifically conducted a survey of 385 respondents to find out coffee drinking habits in Indonesia. The results of this study are price variables, promotions, service quality do not have a significant effect on purchasing decisions and product quality variables, and location has a significant effect on consumer purchasing decisions coffee shops in Gresik City.